Konsep Produksi dan Kebutuhan Konsumen dalam Ekonomi Islam Menurut Umar Ibn Al-Khathab - khoerul Riskon (FAI UMY, 2017)
Konsep Produksi dan Kebutuhan Konsumen dalam Ekonomi Islam Menurut Umar Ibn Al-Khathab